The model of interaction cybernetic organisms and synthesis of optimal strategies keruvannya in cyberspace - Семко, В. В. (Problems of Informatization and Control, 2013)
The question of the formal description of processes in cyberspace. Investigated mathematical principlestaking into account the uncertainties describe the properties of objects of observation in a lineartopological space, as a consequence of the present system. UGA-synthesized halnenu model of interactionof physical and virtual objects in the space of observations.